2000
DOI: 10.1007/s001060050583
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss der mikroneurochirurgischen Operation bei Akustikusneurinom auf dessen Symptome Schwindel und Tinnitus

Abstract: After exstirpation of an acoustic neuroma one trends to concentrated on the preservation of hearing and facial function. But how does the surgical removal for an acoustic neuroma, influence the symptoms of tinnitus and vertigo? Our report follows a retrospective evaluation of 78 patients. Based on these results we will also discuss aspects of the origin of these symptoms. Our patients suffered from tinnitus at a rate of 73% preoperatively and 59% postoperatively. With increasing tumor size tinnitus occurred le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The authors claim that this may be due to a more complete dysfunction of the vestibular nerve in the high-dose group. Another study reports a higher incidence of pre-treatment vertigo in patients with small and medium-sized VSs as compared to large schwannomas (>4 cm; Heerma et al, 2000). In a detailed description of the sensorimotor postural rearrangement after unilateral vestibular deafferentation in patients with VS, Parietti-Winkler et al (2006) found a poorer postural performance of patients before surgery compared to that found 3 months post-operative.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The authors claim that this may be due to a more complete dysfunction of the vestibular nerve in the high-dose group. Another study reports a higher incidence of pre-treatment vertigo in patients with small and medium-sized VSs as compared to large schwannomas (>4 cm; Heerma et al, 2000). In a detailed description of the sensorimotor postural rearrangement after unilateral vestibular deafferentation in patients with VS, Parietti-Winkler et al (2006) found a poorer postural performance of patients before surgery compared to that found 3 months post-operative.…”
Section: Discussionmentioning
confidence: 98%
“…However, only few studies were conducted in a prospective way (Myrseth et al, 2009). Furthermore, although vertigo, dizziness, and unsteadiness of gait are common symptoms of VS (reported incidence between 49 and 66%), these symptoms were often only assessed in a qualitative or semi-quantitative way (El-Kashlan et al, 1998; Lynn et al, 1999; Heerma et al, 2000; Inoue et al, 2001; Humphriss et al, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in developing methods to accurately assess the quality of life (QOL) of patients with VS (2)(3)(4)(5)(6). Vertigo and unsteady gait in those with VS are reported to have an incidence rate ranging from 49 to 66% (7)(8)(9)(10)(11). It is therefore not surprising that balance has been cited as the most significant predictor of QOL for the VS patient population (12)(13)(14)(15).…”
mentioning
confidence: 99%